The role of non-governmental organizations in empowering women political representation in Nigeria - Ewuru, Chinazo Destiny; Ku Samsu, Ku Hasnita; Ismail, Mohd. Mahadee (Human Resource Management Academic Research Society, 2021)
The need for greater women political representation in government through collaborative efforts of non-governmental organizations in Nigeria is long overdue. Non-governmental organizations have a paramount role in ensuring greater political representation of women, especially in developing countries and in Nigeria in particular. Thus, this paper aims to assess the role of non-governmental organizations in empowering greater women political representation in Nigeria and the setback faced by these NGOs. Content analysis technique was employed in this study by using scholarly journals articles. The paper used about twenty scholarly journal articles retrieved from Google Scholar, Web of Science, Sage and other scholar search engine were sourced and used. The findings indicate that increasing women's political representation is achievable through the inclusion of critical stakeholders such as NGOs in the entire electioneering process. The findings also indicate the NGOs in their quest to empower women politically. They are often faced with setbacks such as the absence of political interest amongst the women and the lack of commitment of the critical stakeholders. Thus, the paper recommends the mass orientation and awareness creation of women in and around the country.